2010
DOI: 10.1021/jo100586b
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Origins of Configurational Stability of Axially Chiral Biaryl Amines with an Intramolecular N−H−N Hydrogen Bond

Abstract: Configurationally stable chiral biaryl amines with an intramolecular N-H-N hydrogen bond have been developed. The barriers for racemization are in the range of 19.3-28.2 kcal/mol, which corresponds to the half-lives of racemization of the enantiomers in the range of 7 s to 2 years at 20 degrees C. Enantiomers of some of these compounds were separable by HPLC with chiral stationary phases. The biaryl amines are supposed to have a conformation similar to that of a binaphthyl skeleton, which was indicated by an X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The N-C nonbiaryl atropisomers of our 2-naphthylamine substrates are much more stable than 2-naphthol 35 (Fig. 4), and the intramolecular hydrogen bond 55,56 (conformed by X-ray) would be the important reason. Despite the N-phenyl substituted group was necessary because of π–π interaction in stereo-control in Table 1, the compound 5q (obtained by chiral resolution), which was much easier to form intramolecular hydrogen bond, was used to compare the half-lives of racemization to examine the intramolecular hydrogen bond effect on stereo-stability and gave 514.8 h. These results indicated that the intramolecular hydrogen bond (N-H … O) notably improved the stereo-stability of these N-C axially chiral products.…”
Section: Resultsmentioning
confidence: 89%
“…The N-C nonbiaryl atropisomers of our 2-naphthylamine substrates are much more stable than 2-naphthol 35 (Fig. 4), and the intramolecular hydrogen bond 55,56 (conformed by X-ray) would be the important reason. Despite the N-phenyl substituted group was necessary because of π–π interaction in stereo-control in Table 1, the compound 5q (obtained by chiral resolution), which was much easier to form intramolecular hydrogen bond, was used to compare the half-lives of racemization to examine the intramolecular hydrogen bond effect on stereo-stability and gave 514.8 h. These results indicated that the intramolecular hydrogen bond (N-H … O) notably improved the stereo-stability of these N-C axially chiral products.…”
Section: Resultsmentioning
confidence: 89%
“…Secondary diarylamines, in which steric hindrance is less prominent than in their tertiary analogues, may also exhibit atropisomerism. The Kawabata group reported a series of sterically hindered diarylamines with a single, slowly rotating C−N bond, and demonstrated the importance of an internal hydrogen bond on its barrier to rotation . This strategy of stabilizing configuration through intramolecular hydrogen bonding was elegantly used by Gustafson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Diaryl amines are another nontraditional atropisomeric scaffold that are prevalent throughout drug discovery, particularly among kinase inhibitors, with the FDA-approved vandetanib (18), bosutinib (19) and afatinib (20) representing examples that exist as rapidly interconverting atropisomers. The atropisomerism of diaryl amines has been largely ignored save some seminal work by Kawabata in which his group resolved the atropisomers of a series of diaryl amines and found several to be atropisomeically stable [40,41]. Beyond this, relatively little is known about the factors that render a diaryl amine atropisomerically stable.…”
Section: Interconverting Atropisomers (Class 1) and 'Proatropisomeric' mentioning
confidence: 99%
“…Such tools exist and have been pioneered by LaPlante and coworkers [3]. These tools will especially be useful when dealing with atropisomeric scaffolds that are less well studied such as diaryl ethers [35] and diaryl amines [40,41]. In addition, as more systems are experimentally studied there will be an increased number of datasets of barrier to rotations across sets of pharmaceutically relevant scaffolds which will result in an improved institutional knowledge on what will sufficiently rigidify a specific atropisomeric scaffold.…”
Section: Future Perspectivementioning
confidence: 99%